Analysis of the implementation of the exclusive breastfeeding policy in the working area of Panombean Panei Health Center - Rika Maya Sari Saragih; Sitorus, Rotua Sumihar; Ginting, Desideria Yosepha (JURNAL KESMAS DAN GIZI (JKG), 2024)
Abstract According to Government Regulation No. 33 of 2012 it is stated that Exclusive Breast Milk, hereinafter referred to as Exclusive Breast Milk, is breast milk given to babies from birth for 6 (six) months, without adding and/or replacing it with other food or drinks. . The impact if the mother does not give exclusive breastfeeding, the baby will be at risk of experiencing health problems and being susceptible to infection. This research is a descriptive qualitative research. The research was conducted at the Panombean Panei Health Center. The research informants were 7 people, the samples were taken by snowballing. Data were analyzed in depth in narrative form by means of data reduction, data presentation, drawing conclusions/verification.The results of the study show that the implementation of the exclusive breastfeeding program at the Panombean Panei Health Center has not been maximized, for the last 4 years the average <40% is still far from the national target of 85%. Bureaucratically, the parties responsible for and involved in the exclusive breastfeeding program are the head of the Puskesmas, the MCH program holder, the nutrition program holder, and the village midwife. Recording and reporting is carried out by the village midwife every month and the health center reports to the Simalungun District Office at the beginning of the month. The resources of health personnel in promoting the exclusive breastfeeding program are sufficient. ASI corner is available but not utilized. Facilities and infrastructure for counseling are still lacking such as leaflets and booklets. The source of funds comes from Health Operational Assistance (BOK) combined with other MCH programs. There is no charge for the implementation of the exclusive breastfeeding program. The disposition or attitude of health workers is good and friendly in providing counseling about exclusive breastfeeding, providing information that is easily understood by mothers. Not all mothers can attend posyandu because of work. Supervision is not carried out specifically and the sanctions are only in the form of a warning. Communication in the implementation of the exclusive breastfeeding program was carried out by health workers by going into the field providing counseling or education by cooperating with the village midwife by forming a class for pregnant women and a class for babies. The frequency of counseling is not routine because the area of the Panombean Panei Health Center is wide. Keywords: Application of Policy, Exclusive Breastfeeding Program, Health Center